Lung Metastases From Papillary Thyroid Cancer With Persistently Negative Thyroglobulin and Elevated Thyroglobulin Antibody Levels During Radioactive Iodine Treatment and Follow-Up: Long-Term Outcomes and Prognostic Indicators - Qiu, Zhong-Ling; Shen, Chen-Tian; Sun, Zhen-Kui; Song, Hong-Jun; Zhang, Guo-Qiang; Luo, Quan-Yong (Frontiers in Endocrinology, 2020)
Abstract Background The lung is the most frequent site of distant metastasis from differentiated thyroid cancer (DTC). However, lung metastasis from papillary thyroid cancer (PTC) with persistently negative thyroglobulin (Tg) and elevated Tg antibody (TgAb) levels is an extremely rare entity, and the prognosis is therefore elusive. We investigated the clinical characteristics, long-term outcomes, and prognostic factors of lung metastases in PTC patients with persistently negative thyroglobulin (Tg) and elevated Tg antibody (TgAb) levels during radioactive iodine (131I) treatment and follow-up. Methods We retrospectively reviewed 10,482 patients with DTC who underwent postoperative 131I treatment from 2007 to 2017 at Shanghai Sixth’s People’s Hospital. The relationships between progression-free survival (PFS) and several variables were assessed by univariate and multivariate analyses using the Kaplan–Meier method and a Cox proportional hazards model, respectively. Results Forty-seven patients with PTC were enrolled in this study (4.48‰ of all patients with DTC). The median age at the initial diagnosis of lung metastasis was 39.6±15.4 years, and the patients comprised 14 male and 33 female patients (male: female ratio=1.00:2.36). Twenty-five patients had 131I avidity and 22 had non-131I avidity. At the end of the 5-year follow-up, 12 patients exhibited progressive disease (PD) and 2 patients had died. At the end of the 10-year follow-up, 21 patients showed PD and 5 patients had died. The 5- and 10-year PFS rates were 74.47% and 53.32%, respectively; the 5- and 10-year overall survival (OS) rates were 95.74% and 89.36%, respectively. The timing of lung metastases, maximal size of lung metastases, and 131I avidity were significantly associated with the 5-year PFS rate (P=0.035, P=0.030, and P<0.001, respectively). Only 131I avidity was associated with the 10-year PFS rate (P<0.001). The multivariate analyses also showed that non-131I avidity were the independent poor prognostic factors for 10-year PFS at the end of follow-up (P<0.001). Conclusions Lung metastases from PTC in patients with persistently negative Tg and elevated TgAb levels had an excellent prognosis and survival rate during 131I treatment and follow-up. The loss of 131I avidity remained the strongest independent predictor of a poor prognosis and survival in these patients.